The Implementation of Quality Function Deployment (QFD) in Tire Industry - Hadi, Hari Abdul; Purba, Humiras Hardi; Indarto, Kurnia Sigma; Simarmata, Rorio Gomgom Paska; Putra, Guntur Pratama; Ghazali, Dabith; Aisyah, Siti (Bina Nusantara University, 2017)
This research had two main objectives. The first research objective was to make the right design of new product according to customer requirements with the implementation of Quality Function Deployment (QFD) in the tire industry. The second research objective was to enhance competitiveness based on the renewal of marketing strategy and consumer needs, non-explosive prohibition, non-slip tires, no bulgy, and competitive prices. The research was carried out by using costumer satisfaction rating by comparing with the competitor companies. Based on calculation using QFD method, it shows that split liner has the highest percentage of technical requirement in tire industry about 30,57%. The second factor is pattern design about 25,98%. Then, the third factor is compound technology about 22,68%. Therefore, the researchers can recommend several strategies for the quality improvement based on customer needs for the tire industry.